Transparency, Algorithmic Fairness, and Employee Performance in AI-Based HR: The Moderating Role of Trust in Management - Irvan, Muhammad; Syahroni, Bachrudin; Mahadianto, Moh. Yudi (Indonesian Journal Economic Review (IJER), 2026)
This study examines how perceived transparency and algorithmic fairness in AI-based human resource (HR) practices relate to employee performance, and whether trust in management moderates these relationships. Data were collected through a quantitative cross-sectional survey of 152 employees from Indonesian service organizations using AI-enabled tools in HR decision processes, and analyzed using partial least squares structural equation modeling (PLS-SEM) with bootstrapping. The results show that perceived algorithmic fairness and trust in management have positive and significant relationships with employee performance, whereas perceived transparency does not have a significant direct effect. Trust in management also strengthens the positive relationship between perceived algorithmic fairness and employee performance, but does not significantly moderate the relationship between perceived transparency and employee performance. These findings suggest that organizations seeking performance benefits from AI-based HR should prioritize fairness governance and trust-building managerial practices, while designing transparency as meaningful, employee-relevant explanations rather than merely technical disclosure.